Phenolic Compounds and Antioxidant Activity of Extracts of Nigella sativa L. - Goga, Amila; Hasić, Sabina; Bećirović, Šejla; Ćavar, Sanja (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
Nigella sativa L. (Black cumin) is an annual herbaceous plant which belongs to family Ranunculaceae. The plant commonly grows in the Middle East, Eastern Europe and Western and Central Asia. This plant has been extensively investigated in recent years, due to its notable pharmacological properties. This work presents the investigation of phenolic content and antioxidant activity in extracts obtained from seeds of N. sativa, using Soxhlet and ultrasound extraction techniques. Total phenolics content was measured using the Folin-Ciocalteu method, and they varied from 11.867±0.338 to 31.148±0.293 mg/g GAE. Radical scavenging activity of the samples was examined using two methods, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid), (ABTS) test, and reducing power of these samples was examined by reducing ferric, and molybdenum cations. All examined samples showed prominent antioxidant activity, except p-cymene. Thymoquinone and ethanolic extracts revealed the best results among six investigated samples.